What makes a woman an entrepreneur? / Zuraidah Mohamed Isa...[et al.] - Mohamed Isa, Zuraidah; Ali, Norhidayah; Andin Salamat, Azni Syafena (2010)
Statistics show that there are significantly increasing number of women started their own business over the years. The work flexibility offered by entrepreneurship encourages women to enter the business world. The flexibility or working hours as well as working at home are among reasons why women are interested in joining and owning a business. Other factors such as motivation, personality characteristics, and encouragement from the government, economic condition, political condition and family support motivate them to develop their own business. Although there are many barriers especially when starting a new business, majority of them still survive as per their self-reliant, initiative and never ending give-up. This paper attempts to discuss the factors that contribute to the involvement of women in entrepreneurship.